Analisis Konseptual Konsep Laba dalam Akuntansi Syariah: Integrasi Nilai Keuntungan Dunia dan Keberkahan Akhirat - Lola Ramadhani; A. Syalfana Muthia Reski Amelia Putri; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to clarify the concept of profit in Islamic accounting by emphasizing the importance of integrating worldly gains and blessings in the hereafter amid the rapid development of the Islamic finance industry. This study uses a descriptive qualitative method through a literature review of Islamic accounting literature, reporting standards, and previous research results discussing profit, fairness, and the value of blessings. The results and discussion show that the meaning of sharia profit is not only focused on financial achievements, but also on the quality of contracts, distributive justice, transparency, social contribution, and its conformity with maqāṣid al-sharī‘ah. The analysis shows a gap between the theory of Islamic profit and reporting practices, which still tend to be conventional, so that spiritual and ethical values are not optimally reflected. This study concludes that the reconstruction of the concept of profit requires the refinement of Islamic accounting standards, the strengthening of the role of the Sharia Supervisory Board, the improvement of financial literacy, and the development of an information system capable of capturing indicators of blessing so that profit reporting becomes more comprehensive, accountable, and beneficial.